THE ROLE OF MANAGERIAL COMPETENCIES OF THE HEAD IN ENSURING THE PROFESSIONAL SATISFACTION OF UNIVERSITY EMPLOYEES (Web of Teachers: Inderscience Research, 2024)
Managerial competencies of a manager play a key role in the formation of professional satisfaction of employees of a higher educational institution. These competencies affect the organizational culture, motivation of employees, their involvement in the work process and the overall level of job satisfaction.